Cellulose nanocrystals as nucleating agents for the strain induced crystallization in natural rubber. Issue 45 (9th November 2022) - Candau, Nicolas; Fernandes, João Paulo Cosas; Vasmer, Emilien; Maspoch, Maria Lluisa
Abstract : Dispersed cellulose nanocrystals enhance strain induced crystallization in the natural rubber matrix and lead to improved elastocaloric performance. Abstract : Vulcanized natural rubber (NR)/cellulose nanocrystals (CNC) composites with a CNC content of up to 5 wt% using physical blending and dicumyl peroxide crosslinking were prepared. The tensile properties were investigated at slow and high strain rates. The slow strain rate tests revealed an increase of the elastic modulus concomitant with a decrease of strain at the crystallization onset while increasing the CNC fraction. The high strain rate tests performed near adiabatic conditions demonstrated the ability of the CNC to improve the elastocaloric properties of the NR matrix, with an increase of 30% and 15% of heating and cooling capacities, respectively, in the presence of 3 wt% CNC. Such results were ascribed to (i) a higher thermoelastic effect, due to strain amplification in the NR matrix in the presence of CNC and (ii) a nucleating effect of the CNC on strain induced crystallization. This series of materials can be proposed as a promising eco-friendly alternative to conventional carbon black filled rubber as potential green elastocaloric materials (heating pump, cooling machines).